A Review of Solar-Powered Boat Development - Kurniawan, Adi (IPTEK The Journal for Technology and Science, 2025)
Research in the application of renewable energy has intensified in recent years. The possibility of petroleum extinction in the future is forcing researchers to enhance the utilization of renewable energy resources as substitute for fossil fuel-based technologies in all fields. Ships as one of the most important transportation in the world also require diesel oil as fuel for main propulsion systems and for diesel generators which supply electrical needs. Solar energy has been considered as the most suitable renewable energy resources to substitute the role of fuel in the ships. In this paper, the latest research on the utilization of solar energy in the ship are presented and analyzed to provide information for the researchers who developed the technology of solar-powered boat. The best possible method to utilize the solar energy in the ship is by using catamaran boat with the flat top structure to provide room for placing solar panel. Furthermore, the solar energy extracted from the panel can be optimized by using quadratic Maximization Maximum Power Point Tracking (MPPT) that executed by KY converter, and converted to AC voltage using a multilevel inverter. The use of quadratic MPPT with KY converter is expected to generate a high output power with small DC voltage ripple from the solar panel while the use of a multilevel inverter is expected to convert the DC voltage into high-efficiency AC voltage before supplied to the electric motor propulsion system.